2016
DOI: 10.1038/srep33835
|View full text |Cite
|
Sign up to set email alerts
|

Effect of graphene oxide ratio on the cell adhesion and growth behavior on a graphene oxide-coated silicon substrate

Abstract: Control of living cells on biocompatible materials or on modified substrates is important for the development of bio-applications, including biosensors and implant biomaterials. The topography and hydrophobicity of substrates highly affect cell adhesion, growth, and cell growth kinetics, which is of great importance in bio-applications. Herein, we investigate the adhesion, growth, and morphology of cultured breast cancer cells on a silicon substrate, on which graphene oxides (GO) was partially formed. By minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 30 publications
(45 reference statements)
2
29
0
Order By: Relevance
“…Another important parameter to consider when determining uptake parameters is adhesion. Different studies have pointed out that the adhesive force among biological membranes and graphene decreases at higher oxidation states 36,37 . Furthermore, hydrophobic materials are more likely to adhere to the lipid bilayers of cell membranes 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Another important parameter to consider when determining uptake parameters is adhesion. Different studies have pointed out that the adhesive force among biological membranes and graphene decreases at higher oxidation states 36,37 . Furthermore, hydrophobic materials are more likely to adhere to the lipid bilayers of cell membranes 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Therefore, despite the concerns due to toxicity, graphenebased nanomaterials and scaffolds have been used successfully in animal and in vitro models of bone defects and assays. [28][29][30][31][32][33][34][35][36][37][38] Even though the results of the in vitro assays and animal models described above are encouraging and strengthen the use of graphene derivatives in biomedicine, the biocompatibility and cytotoxicity of graphene nanoparticles is altered by parameters, such as surface functionalization, shape, size, dose, cell type, and the experimental design. As a result, more research is warranted before the nanoparticles can be used effectively in a human clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…2(a,b) . Our previous study suggested that this treatment plays an important role in streptavidin (STR, Sigma-Aldrich, USA) immobilization on topographical substrates because the hydroxyl groups provide the nanostructured arrays with enhanced conjugation with 3-APTES (Sigma-Aldrich, USA) 33 , 44 . After rinsing with an ethanol solution for 10 min, the GaN MPs were placed on a hot plate at 120 °C for 10 min and reacted with 12.5% (v/v) GA (Sigma-Aldrich, USA) in distilled water on the 3D-rocker for 4 h, leading to the immobilization of the aldehyde group on the APTES-coated GaN MPs (Fig.…”
Section: Resultsmentioning
confidence: 99%